Slot Loaded Capacitive fed Suspended RMSA with Meandered Ground Plane - Ravi M. Yadahalli; Nandini M. Ammanagi (International Journal of Informatics and Communication Technology (IJ-ICT), 2018)
In this paper, variations in the Capacitive fed suspended RMSA configurations have been proposed. Initially, the reference antenna consists of rectangular patch of size of (35.5 X 45.6) mm2 and a small rectangular feed patch of size of (1.4 X 4) mm2 residing on the same substrate suspended above the ground plane. Coaxial probe is used to feed the small patch which in turn excites the radiator patch electromagnetically, yielding a large impedance bandwidth (BW) of 39%, with good gain and broadside radiation pattern.  By, meandering the ground plane of reference antenna with three rectangular slots, the prototype antenna is fabricated and measurement has been carried out to validate the result for compact broadband response. Later, by loading a pair of rectangular slots in the radiating patch of the reference antenna in addition to the rectangular slots in the ground plane, the prototype antenna is fabricated and measurement has been carried out to validate the result for compact dual band response.